Strategic management in retailing business on bumiputra entrepreneurs under the goverment's development scheme - Mohd Faudzi, Musa. (2002)
The purpose of this research is to study the effects of the hypermarkets on retailers and in particular to Bumiputra Retailers under the PROSPER program. Even though several studies has been done concerning this matter but none of them have put up a distinct emphasis on the Bumiputra retailers and especially study on their ability and skills in order to remain competitive in the new concepts of retailing business.